(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The report investigates the role of power density of melting and evaporation and speed to realize several laser technological processes on copper samples for a fibre laser and a CuBr laser. A methodology has been developed to determine preliminary operating intervals of power density for different speeds for the laser marking, laser ablation and laser texturing processes. From theoretical calculations, graphics of the dependences of the critical power density of melting and evaporation on the speed were drawn. Areas where oxidation, melting or evaporation occur were defined. Comparing the theoretical results and the obtained experimental results shows a very good convergence between them for both laser sources.